2018
DOI: 10.3389/fvets.2018.00109
|View full text |Cite|
|
Sign up to set email alerts
|

Bovine Tuberculosis in Britain and Ireland – A Perfect Storm? the Confluence of Potential Ecological and Epidemiological Impediments to Controlling a Chronic Infectious Disease

Abstract: Successful eradication schemes for bovine tuberculosis (bTB) have been implemented in a number of European and other countries over the last 50 years. However, the islands of Britain and Ireland remain a significant aberration to this trend, with the recent exception of Scotland. Why have eradication schemes failed within these countries, while apparently similar programs have been successful elsewhere? While significant socio-economic and political factors have been discussed elsewhere as key determinants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
118
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(135 citation statements)
references
References 193 publications
3
118
0
Order By: Relevance
“…This may impact the nexus between fascioliasis and bovine tuberculosis infection (Kelly et al, ; Munyeme et al, ). Wild populations may also be governed by differing ecological rules than that of managed populations (Ezenwa & Jolles, ; Graham, ), as managed populations have a very strong evolutionary pressure on the pathogen due to test and cull (as is the case of bTB in Northern Ireland), and so too on detected infected hosts (Allen et al, ). For example, Ezenwa and Jolles () found that anthelminthic treatment of free‐ranging buffalo in South Africa resulted in increased animal survival, which then led to increases in bTB risk for the population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may impact the nexus between fascioliasis and bovine tuberculosis infection (Kelly et al, ; Munyeme et al, ). Wild populations may also be governed by differing ecological rules than that of managed populations (Ezenwa & Jolles, ; Graham, ), as managed populations have a very strong evolutionary pressure on the pathogen due to test and cull (as is the case of bTB in Northern Ireland), and so too on detected infected hosts (Allen et al, ). For example, Ezenwa and Jolles () found that anthelminthic treatment of free‐ranging buffalo in South Africa resulted in increased animal survival, which then led to increases in bTB risk for the population.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have impact for both policy makers and practitioners invested in the management bovine tuberculosis in endemic regions, which rely upon the accurate diagnosis of infected individuals (Allen et al, ; De la Rua‐Domenech et al, ; Schiller et al, ). Co‐infection management has been proposed as an important policy approach when moving towards eradication of notifiable pathogens (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycobacterium bovis, a member of the M. tuberculosis complex, causes bovine tuberculosis, one of the most important veterinary health problems in the UK and Ireland [1,2]. It is also a neglected zoonotic infection in humans, causing an estimated 147,000 new infections and 12,500 deaths worldwide in 2016 [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, bTB has been the focus of ongoing national, and various regional, eradication programs in both the UK and Ireland for over 50 years. Despite these programs, bTB remains a significant burden due to its complex epidemiology (Allen, Skuce, & Byrne, ).…”
Section: Introductionmentioning
confidence: 99%